Tableware

JP7635250B2Active Publication Date: 2025-02-25NORITAKE MACHINE TECHNO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022550171
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-30
Filing Date
2022-07-27
Publication Date
2025-02-25
Estimated Expiration
2042-07-27

AI Technical Summary

Benefits of technology

【0011】 ここに開示されるセラミックス製品は、装飾膜の表面を対象としたFESEM-EDS分析において、貴金属元素の質量濃度CNに対する希土類元素の質量濃度CRの割合(CR/CN)が0.01以上となるように構成されている。これによって、耐アルカリ性低下の要因となる貴金属元素に対して、耐アルカリ性向上の要因となる希土類元素が一定以上存在するため、装飾膜の耐アルカリ性を好適な範囲に維持できる。一方で、ここに開示されるセラミックス製品は、上記CR/CNの上限値が0.18以下となるように構成されている。これによって、多量の希土類元素が存在することによる耐酸性の低下を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007635250000010
    Figure 0007635250000010
  • Figure 0007635250000011
    Figure 0007635250000011
  • Figure 0007635250000001
    Figure 0007635250000001
Patent Text Reader

Abstract

The present invention provides a ceramic product which has satisfactory chemical resistance and rarely undergoes the breakage of a decorative film during washing. The technique disclosed herein provides a ceramic product having a decorative film containing a noble metal element and a matrix-forming element. The matrix-forming element in the ceramic product comprises at least a rare earth element. In the ceramic product disclosed herein, the mass-based concentration CN of the noble metal element as measured by an FESEM-EDS analysis of the surface of the decorative film is 11% to 70% inclusive, and the ratio of the mass-based concentration CR of the rare earth element to the mass-based concentration CN of the noble metal element (i.e., CR / CN) is 0.01 to 0.18 inclusive. The decorative film in the ceramic product has both of alkali resistance and acid resistance at high levels and therefore has satisfactory chemical resistance, and can be prevented from the breakage thereof during washing.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ceramic product. More specifically, the present invention relates to a ceramic product having a decorative film containing a precious metal element and a matrix-forming element. This application claims priority based on Japanese Patent Application No. 2021-140391 filed on August 30, 2021, the entire contents of which are incorporated herein by reference. [Background technology]

[0002] A decorative film containing a precious metal element may be formed on the surface of ceramic products such as porcelain, glassware, and enamelware to give an elegant or luxurious impression. This type of decorative film is formed by applying a decorative composition containing specific components to the surface of the ceramic product and then performing a firing process. One example of such a decorative composition is a metal resinate (a metal organic compound) containing a precious metal element and a matrix-forming element. When such a decorative composition is fired, a decorative film containing an amorphous region and a precious metal region is formed. In this amorphous region, an amorphous matrix (typically a glass matrix) is formed with a skeleton of oxides of specific metal elements and semimetal elements (matrix-forming elements).

[0003] Among these ceramic products, there are some (e.g., tableware, etc.) that are expected to be heated in a microwave oven. If the decorative film of this ceramic product contains a large amount of precious metal, high-frequency electromagnetic waves (e.g., a frequency of about 2.45 GHz) may cause sparks and damage the decorative film. For this reason, in recent years, microwave-safe ceramic products with a reduced content of precious metals in the decorative film have been proposed. An example of a decorative composition (overglaze paste) for forming this type of decorative film is disclosed in Patent Document 1. In the overglaze paste described in Patent Document 1, the content of precious metal powder is adjusted to 20% by weight or more and less than 50% by weight, and the particle size of the precious metal powder is adjusted to 0.4 μm or more and 2 μm or less. When such an overglaze paste is fired, a precious metal layer dispersed in a polka dot pattern is formed on the surface of the insulating article (substrate). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent No. 4757434 [Non-patent literature]

[0005] [Non-Patent Document 1] "Study on Rare Earth Silicate Glasses", Inorganic Materials Research Institute Research Report No. 42, Science and Technology Agency (1985) Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, there has been a demand for the development of technology that can adequately prevent damage (peeling, cracks, etc.) to decorative films when ceramic products are washed. Specifically, the amorphous regions of decorative films have poor chemical resistance, and therefore may be damaged when washed in a high-temperature environment using a strong alkaline detergent (e.g., washing in an automatic dishwasher) or when immersed in an acidic detergent for a long period of time. In particular, decorative films on microwave-safe ceramic products tend to be even more susceptible to the above-mentioned damage during washing, since the continuity of the precious metal regions is lost and the amorphous regions are easily exposed.

[0007] In order to solve the above-mentioned problems, the present inventors have considered the inclusion of rare earth elements in the amorphous region of the decorative film. Specifically, it is known that the alkali resistance of amorphous materials such as glass can be improved by the presence of rare earth elements in the amorphous matrix (see Non-Patent Document 1). It is believed that the effect of improving the alkali resistance is caused by the mesh structure being tightened by doping rare earth elements with high oxygen affinity into the amorphous matrix, thereby suppressing the penetration of alkaline ions. In addition, it is believed that rare earth oxides also have the effect of suppressing alkali erosion because they remain and form a film even after other components are eluted by exposure to alkaline chemicals. However, in the ceramic products having the above-mentioned configuration, it was sometimes impossible to form a decorative film with sufficient alkali resistance, despite the rare earth elements being contained in the amorphous region.

[0008] The present invention has been made in consideration of the above circumstances, and has an object to provide a ceramic product that has sufficient chemical resistance and can suppress damage to a decorative film during cleaning. [Means for solving the problem]

[0009] The present inventors have conducted various studies to solve the above-mentioned problems, and have found that the decorative film for ceramic products having the above-mentioned configuration is more susceptible to deterioration in alkali resistance than ordinary amorphous materials because it contains precious metal elements. Specifically, precious metal elements are added to decorative films for ceramic products to create an excellent aesthetic appearance. However, since this type of precious metal element has a strong catalytic action, it is likely to promote deterioration in alkali resistance due to hydrolysis of the amorphous matrix. On the other hand, decorative films to which a large amount of rare earth elements are added to compensate for the deterioration in alkali resistance caused by the precious metal elements are likely to have a significantly decreased acid resistance. In other words, in order to improve the overall chemical resistance of decorative films for ceramic products, it is necessary to have a mass concentration C of precious metal elements of 1000 to 150 ... N and the mass concentration of rare earth elements C R Ratio of (C R / C N ) needs to be appropriately controlled.

[0010] The technology disclosed herein has been made based on the above findings. The technology disclosed herein provides a ceramic product having a decorative film containing a precious metal element and a matrix-forming element. The matrix-forming element of the ceramic product contains at least a rare earth element. The ceramic product disclosed herein has a mass concentration C of the precious metal element obtained by FESEM-EDS analysis of the surface of the decorative film. N is 11% or more and 70% or less, and the mass concentration of the precious metal element C N Mass concentration of rare earth elements C R The ratio of (C R / C N ) is greater than or equal to 0.01 and less than or equal to 0.18.

[0011] The ceramic product disclosed herein has a mass concentration of precious metal elements C N Mass concentration of rare earth elements C R The ratio of (C R / C N ) is 0.01 or more. This allows the presence of a certain amount of rare earth elements, which are a factor in improving alkali resistance, in contrast to the presence of precious metal elements, which are a factor in reducing alkali resistance, so that the alkali resistance of the decorative film can be maintained within a suitable range. R / C N The upper limit of the rare earth element content is set to 0.18 or less. This makes it possible to suppress the deterioration of acid resistance caused by the presence of a large amount of rare earth element.

[0012] In addition, as a result of experiments conducted by the inventors, the mass concentration C N It has been confirmed that if the mass concentration C of the precious metal element is too low, the chemical resistance (especially the acid resistance) of the decorative film is reduced. NIt has been confirmed that if the amount of C is too large, the gloss of the decorative film is significantly reduced, and the aesthetic appearance of the ceramic product is impaired. In consideration of these points, in the ceramic product disclosed herein, the mass concentration C of the precious metal element in the FESEM-EDS analysis of the surface of the decorative film is N is controlled to between 11% and 70%.

[0013] In this specification, the term "mass concentration" refers to the relative mass of any metal element (or metalloid element) when the "total mass of metal elements and metalloid elements" obtained by performing FESEM-EDS (field emission scanning electron microscope-energy dispersive X-ray analysis) on the surface of the decorative film is taken as 100%. The measurement procedure for the "mass concentration" is as follows. First, the surface of the decorative film (typically a flat surface) is observed using a field emission scanning electron microscope (FESEM) equipped with an energy dispersive X-ray analysis (EDS) device. Then, after adjusting the observation position so that the decorative film is reflected in the entire field of view of 5000 times magnification (field of view: 25.5 μm × 19.2 μm), a qualitative analysis chart of the metal elements and metalloid elements is obtained using the EDS device. Then, the metal elements and metalloid elements are specified in the obtained qualitative analysis chart, and the relative concentration of the desired element is calculated based on a predetermined quantitative correction method (for example, the standardless method). This allows the mass concentration of the desired element to be obtained. In addition, in the FESEM-EDS analysis of the surface of the decorative film, elements located at a depth of several hundred to several thousand nm from the surface of the decorative film are detected, so that the constituent elements of the layer (substrate or coating layer) located below the decorative film may be reflected in the measurement results. In other words, the "mass concentration" in this specification does not mean "the mass concentration of any element contained in the decorative film" but "the mass concentration of any element detected in the FESEM-EDS analysis of the surface of the decorative film". In addition, it has been confirmed by the inventors' experiments that when the mass concentration of a certain element in the FESEM-EDS analysis of the surface of the decorative film satisfies the above-mentioned conditions, a ceramic product having sufficient chemical resistance and capable of suppressing damage to the decorative film during cleaning can be obtained.

[0014] In a preferred embodiment of the ceramic product disclosed herein, the matrix-forming elements further contain at least one first element selected from the group consisting of Zr, Ti, and Co. These first elements can contribute to improving the chemical resistance of the decorative film.

[0015] In the embodiment in which the decorative film contains the first element, the mass concentration C of the rare earth element obtained by FESEM-EDS analysis of the surface of the decorative film is R Mass concentration of the first element C 1 The ratio of (C 1 / C R ) is preferably 3 or less. As described above, the first element can contribute to improving the chemical resistance of the decorative film. However, the mass concentration C 1 If the amount of rare earth elements becomes too large, the mass concentration C R In view of this, in this embodiment, the above C 1 / C R This limits the upper limit of the

[0016] In a preferred embodiment of the ceramic product disclosed herein, the decorative film contains at least one precious metal element selected from the group consisting of Pt, Au, Pd, Rh, Ir, and Ag. These precious metal elements can contribute to the formation of a decorative film with excellent appearance.

[0017] In a preferred embodiment of the ceramic product disclosed herein, the mass concentration C of the precious metal element N Mass concentration of Pt with respect to C Pt The ratio of (C Pt / C N ) is 0.75 or more. Platinum (Pt) exhibits particularly excellent color development among the above-mentioned precious metal elements, and therefore can be suitably used for forming decorative films with excellent aesthetics. However, since Pt has a stronger catalytic action than other precious metal elements (e.g., Au, etc.), it is particularly likely to promote hydrolysis of the amorphous matrix. However, in the technology disclosed herein, as described above, the mass concentration C N Mass concentration of rare earth elements C R The ratio of (C R / CN ) is appropriately controlled, it is possible to form a decorative film with sufficient alkali resistance even when the main component of the precious metal element is Pt.

[0018] In a preferred embodiment of the ceramic product disclosed herein, the decorative film contains at least one rare earth element selected from the group consisting of Y, Sm, La, Ce, Pr, Nd, and Dy. By containing these rare earth elements, the deterioration of alkali resistance caused by precious metal elements can be particularly effectively suppressed.

[0019] In a preferred embodiment of the ceramic product disclosed herein, the matrix-forming element further contains at least one second element selected from the group consisting of Si, Al, K, Na, Mg, Ca, Ga, Ba, and Bi, which allows the construction of an amorphous matrix suitable for the decorative film.

[0020] In a preferred embodiment of the ceramic product disclosed herein, the decorative film comprises a precious metal region containing a precious metal element as a main component and an amorphous region containing a matrix-forming element as a main component, and a plurality of precious metal regions are interspersed in the amorphous region. This allows each precious metal region to be insulated by the amorphous region, so that the decorative film can be prevented from being damaged by sparks when using a microwave oven. Note that the microwave-safe ceramic product having the above configuration has a large amount of exposed amorphous region, so that the chemical resistance of the decorative film is easily reduced. However, according to the technology disclosed herein, a decorative film having sufficient chemical resistance can be formed even on this type of microwave-safe ceramic product. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a diagram illustrating a cross-sectional structure of a ceramic product according to one embodiment. [Diagram 2] FIG. 2 is an example of a histogram in which the horizontal axis represents the brightness value of a secondary electron image of a cut surface of a ceramic product, and the vertical axis represents the number of counts. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] A preferred embodiment of the technology disclosed herein will be described below. Matters other than those specifically mentioned in this specification that are necessary for implementation (for example, detailed preparation means for decorative compositions and manufacturing procedures for ceramic products) can be understood based on the technical content taught by this specification and the general technical common sense of a person skilled in the art in the relevant field. The content of the technology disclosed here can be implemented based on the content disclosed in this specification and the general technical common sense of the art in the relevant field. In this specification, the expression "A to B" indicating a range means A or more and B or less. Therefore, it includes the case where it is more than A and less than B.

[0023] <Ceramics products> Hereinafter, one embodiment of the ceramic product disclosed herein will be described. Fig. 1 is a diagram showing a cross-sectional structure of the ceramic product according to this embodiment. As shown in Fig. 1, this ceramic product 1 includes a substrate 10, a coating layer 20, and a decorative film 30. Each of these will be described in detail below.

[0024] 1. Base material The substrate 10 is a molded body mainly composed of ceramics. Examples of ceramics for the substrate 10 include silica, alumina, zirconia, ceria, yttria, boronia, magnesia, and calcia. The thickness, shape, color, hardness, and other properties of the substrate 10 can be appropriately changed depending on the application of the ceramic product 1, and are not intended to limit the technology disclosed herein, so detailed explanations will be omitted.

[0025] 2. Coating layer The coating layer 20 is a layer mainly composed of an amorphous material (typically glass) and is formed on the surface of the substrate 10 to improve the aesthetic appearance (particularly the gloss) and to protect the substrate 10. The coating layer 20 is formed, for example, by applying a glaze to the surface of the substrate 10 and then firing the glaze. Such a glaze is an agent containing metal elements and metalloid elements that become oxides upon firing and form an amorphous matrix. The glaze may contain the same elements as those contained in the amorphous region 34 of the decorative film 30, or may contain different elements.

[0026] The composition of the coating layer 20 is not particularly limited as long as it does not significantly impair the effects of the technology disclosed herein, and any conventionally known components that can be used in protective layers for ceramic substrates can be appropriately selected. As an example, the coating layer 20 can essentially contain Si, Al, Fe, Mg, Na, Zn, K, Ca, Sn, etc. as constituent elements. These constituent elements can form an amorphous matrix in the form of oxides. That is, the coating layer 20 can contain silicon oxide (SiO 2 ), aluminum oxide (Al 2 O 3 ), iron oxide (Fe 2 O 3 ), magnesium oxide (MgO), potassium oxide (Na 2 O), zinc oxide (ZnO), potassium oxide (K 2 O), calcium oxide (CaO), tin oxide (SnO 2 ) and the like can be constructed. Note that the abundance ratio of each of the above-mentioned elements in the coating layer 20 does not limit the technology disclosed herein, and therefore a detailed description thereof will be omitted.

[0027] 3.Decorative film As shown in FIG. 1, the ceramic product 1 according to this embodiment has a decorative film 30. The decorative film 30 is formed on the surface of the coating layer 20. Although not shown, the decorative film 30 is formed to present a desired pattern (including letters and pictures) in a plan view with the aim of improving the aesthetic appearance of the ceramic product 1. The decorative film 30 contains a precious metal element and a matrix-forming element, which will be described later. Typically, the decorative film 30 includes a precious metal region 32 and an amorphous region 34.

[0028] The precious metal region 32 is a region containing a precious metal element as a main component, which will be described later. This precious metal region 32 mainly contributes to the coloring of the decorative film 30. In this specification, the "precious metal region containing a precious metal element as a main component" refers to a region with the highest brightness at the peak of a histogram obtained by image analysis of a cross section of a ceramic product. In this image analysis, first, the ceramic product is cut along the thickness direction of the decorative film, and the cut surface is fixed by resin embedding processing and then polished by ion milling. Next, in a state where the polished surface is fixed to a sample stage with carbon tape so that it faces upward, an osmium plasma coater (manufactured by Nippon Laser & Electronics Co., Ltd.: OPC80N) is used to coat the cut surface, thereby preparing a measurement sample with an osmium-coated cut surface. In addition, the discharge voltage for the osmium coating is 1.2 kV, the degree of vacuum is 6 to 8 Pa, and the coating time is 10 seconds. Next, a secondary electron image of the cut surface of the decorative film is obtained using a field emission scanning electron microscope (manufactured by Hitachi High-Tech Corporation: SU8230). The accelerating voltage for acquiring the secondary electron image is 2.0 kV, the emission current is 10±0.5 μA, and the field of view is 50,000 to 100,000 times. Next, the acquired secondary electron image is subjected to noise removal using the image processing software image J (ver.1.53e) with a Gaussian filter set to sigma = 2 to 5. In this specification, the region in the image after the noise removal in which the brightness value is 125 or more is regarded as a "precious metal region containing precious metal elements as the main component". When the brightness value of the image after the noise removal is plotted on the horizontal axis and the count number on the vertical axis as a histogram, four peaks of different brightness are confirmed (see FIG. 2). These four peaks correspond to the four regions of the embedding resin, the base material, the amorphous region, and the precious metal region in descending order of brightness, and the region with the highest brightness corresponds to the precious metal region. The threshold value for determining whether or not the region is a precious metal region (brightness of 125 or more in FIG. 2) is set based on such histogram analysis.

[0029] On the other hand, the amorphous region 34 is a region that contributes to the fixation and protection of the precious metal region 32. In this amorphous region 34, an amorphous matrix is ​​formed with an oxide of a matrix-forming element as a skeleton. In this specification, the term "matrix-forming element" is a concept that includes metal elements and metalloid elements that can construct an amorphous matrix in the oxide state. In addition, the term "amorphous matrix" refers to a structure in which an amorphous oxide (oxide with an amorphous structure) of a specific metal element and metalloid element forms a skeleton, and various metal elements (or metalloid elements) exist in the skeleton as oxides or in the form of cations. An example of a material (amorphous material) having such an amorphous matrix is ​​glass. In this specification, the "amorphous region containing a matrix-forming element as a main component" is a region in which the second highest brightness is confirmed in the image analysis of the cut surface of the above-mentioned ceramic product.

[0030] In addition, the decorative film 30 is not limited to a layer consisting of only the precious metal region 32 and the amorphous region 34 as shown in Fig. 1. For example, particles (crystalline particles) mainly composed of crystalline metal oxide may be dispersed in the amorphous region 34. Even when the decorative film 30 containing such crystalline particles is formed, the effect of the technology disclosed herein (improved chemical resistance) can be adequately exhibited.

[0031] The thickness T of the decorative film 30 is preferably 30 nm or more and 250 nm or less. The ceramic product 1 on which such a thin decorative film 30 is formed can achieve excellent aesthetics at low cost, but the decorative film 30 is very likely to peel off, and even slight peeling of the decorative film 30 may significantly impair the aesthetics. However, according to the technology disclosed herein, the chemical resistance of the decorative film 30 can be improved and peeling of the decorative film 30 due to exposure to chemicals (detergent, etc.) can be suppressed. That is, the technology disclosed herein can be particularly suitably applied to the ceramic product 1 having a thin decorative film 30. In addition, the "thickness T of the decorative film" in this specification refers to the distance from the surface 30a of the decorative film 30 to the deepest position where the precious metal region 32 exists, as shown in FIG. 1. When the coating layer 20 mainly composed of an amorphous material exists between the substrate 10 and the decorative film 30 as in this embodiment, a clear boundary may not be formed between the decorative film 30 (amorphous region 34) and the coating layer 20. For this reason, in this specification, for the sake of convenience, the portion where the precious metal region 32 exists is regarded as the decorative film 30 .

[0032] In the ceramic product 1 shown in FIG. 1, a plurality of precious metal regions 32 are scattered in the amorphous regions 34. As a result, each precious metal region 32 is insulated by the amorphous regions 34, so that it is possible to appropriately prevent sparks from occurring when the microwave oven is used. On the other hand, this type of microwave-safe ceramic product has a large amount of exposed amorphous regions, so the chemical resistance of the decorative film is likely to decrease. However, the ceramic product 1 according to this embodiment is a microwave-safe ceramic product, but is provided with a decorative film 30 that has excellent chemical resistance. The composition of the decorative film 30 that realizes such excellent chemical resistance will be described below.

[0033] (1) Noble metal elements The precious metal element is a component that contributes to the coloring of the decorative film 30. As described above, the precious metal element is the main component of the precious metal region 32. However, the location of the precious metal element in the decorative film 30 is not a factor that limits the technology disclosed herein. That is, depending on the manufacturing conditions, a part of the precious metal element may be mixed into the amorphous region 34. Examples of the precious metal element include platinum (Pt), gold (Au), palladium (Pd), rhodium (Rh), iridium (Ir), silver (Ag), ruthenium (Ru), and osmium (Os).

[0034] Here, the ceramic product 1 according to this embodiment has a mass concentration C N The first feature is that the mass concentration C of the precious metal element is controlled to 11% or more and 70% or less. This makes it possible to form a decorative film 30 that is aesthetically pleasing and prevents a significant decrease in chemical resistance (particularly acid resistance). Specifically, the mass concentration C of the precious metal element is controlled to 11% or more and 70% or less in the surface 30a of the decorative film 30 by FESEM-EDS analysis. N It has been confirmed through experiments that, when the mass concentration C of the precious metal element is small, the deterioration of the alkali resistance due to the catalytic action of the precious metal element is unlikely to occur, but the acid resistance of the decorative film 30 is likely to deteriorate. N By making the mass concentration C of the precious metal element 11% or more, a significant decrease in acid resistance is prevented. N is preferably 11.5% or more, more preferably 12% or more, even more preferably 12.5% ​​or more, and particularly preferably 13% or more. Furthermore, if the amount of the precious metal element contained in the decorative film 30 is reduced, the aesthetic appearance of the ceramic product 1 may be deteriorated due to a decrease in the color-developing components. However, the mass concentration C of the precious metal element in the FESEM-EDS analysis of the surface 30a of the decorative film 30 N It has also been confirmed that when the content is 11% or more, a decorative film 30 with favorable color development can be formed.

[0035] On the other hand, the mass concentration of precious metal elements C NIt has been confirmed that if the mass concentration C of the precious metal element is too high, the gloss of the decorative film 30 decreases, and the aesthetic appearance of the ceramic product 1 is impaired. This is presumably because, in a decorative film with too much precious metal element present, the particle size of the precious metal particles becomes too large due to over-sintering, causing the decorative film to become cloudy. From this perspective, in this embodiment, the mass concentration C of the precious metal element is set to 1000 ppm. N In order to obtain a ceramic product 1 with a better appearance, the mass concentration of the precious metal elements C N is preferably 69.5% or less, more preferably 69% or less, even more preferably 68.5% or less, and particularly preferably 68% or less.

[0036] Among the above-mentioned precious metal elements, platinum (Pt) has particularly excellent color development, and is therefore suitable for forming a decorative film 30 with excellent aesthetics. For example, a microwave-safe ceramic product 1 such as that of this embodiment has a problem in that the decorative film 30 tends to look dark because the continuity of the precious metal region 32 is lost. However, by using Pt as the main component of the precious metal element, a decorative film 30 with excellent color development can be formed even on a microwave-safe ceramic product 1. On the other hand, since Pt has a stronger catalytic action than other precious metal elements (e.g., Au, etc.), it is particularly likely to promote a decrease in alkali resistance due to hydrolysis of the amorphous matrix. However, in the ceramic product 1 of this embodiment, in order to compensate for the decrease in alkali resistance of the decorative film 30 caused by the precious metal element (Pt), the C described below is used. R / C N The ratio of Pt is controlled within an appropriate range. Therefore, according to this embodiment, even when Pt is used as the main component of the precious metal elements, a decorative film 30 having sufficient alkali resistance and excellent color development can be formed. Note that, in this specification, "containing Pt as the main component of the precious metal elements" refers to the mass concentration C of all precious metal elements confirmed by FESEM-EDS analysis of the surface of the decorative film. N Mass concentration of Pt with respect to C Pt The ratio of (C Pt / C N ) is 0.75 or more (preferably 0.85 or more, and more preferably 0.95 or more).

[0037] (2) Matrix-forming elements As described above, the matrix-forming element is a metal element or a metalloid element that can build an amorphous matrix in the oxide state. However, like the above-mentioned precious metal elements, the location of the matrix-forming element in the decorative film 30 does not limit the technology disclosed herein. That is, depending on the manufacturing conditions, some of the elements that can be considered as matrix-forming elements may be mixed into the precious metal region 32. Examples of the matrix-forming elements include Al, Ti, Zr, Si, Bi, Sm, Y, La, Ce, Pr, Nd, Sm, Dy, Sn, Zn, Be, Mg, Ca, Sr, Ba, Li, Na, K, Rb, B, V, Fe, Cu, P, Sc, Pm, Eu, Gd, Tb, Ho, Er, Tm, Yb, Lu, Ni, In, Co, and Cr. Note that some of the above-mentioned precious metal elements (such as Ag) are oxidized in the firing process to form an amorphous matrix. However, for the sake of convenience, in this specification, the elements listed in the above (1) noble metal elements are not considered to be matrix forming elements. M " refers to the mass concentration of metal elements and metalloid elements capable of forming an amorphous matrix, excluding noble metal elements.

[0038] Although not limiting the technology disclosed herein, the mass concentration C of the matrix-forming element in the FESEM-EDS analysis of the surface 30a of the decorative film 30 M is preferably 20% or more, more preferably 22.5% or more, even more preferably 25% or more, and particularly preferably 27.5% or more. This allows the formation of a decorative film 30 that has a sufficient amount of amorphous regions 34 and exhibits excellent gloss. On the other hand, the mass concentration C of the matrix-forming element M is preferably 50% or less, more preferably 47.5% or less, and particularly preferably 45% or less. This ensures a certain amount of the precious metal region 32 and allows the formation of a decorative film 30 with excellent color development.

[0039] Next, elements that can be contained in the decorative film 30 as matrix-forming elements will be specifically described.

[0040] (a) Rare earth elements First, the decorative film 30 in this embodiment contains at least a rare earth element as a matrix forming element. The rare earth element can be selected from among scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu) without any particular limitation. These rare earth elements have high oxygen affinity, so that the mesh structure can be tightened by being doped into the amorphous matrix. In addition, the rare earth oxide remains and forms a coating even after other components are dissolved by exposure to an alkaline agent. This makes it possible to prevent alkali from penetrating into the amorphous region 34 and damaging the decorative film 30. Among the above-mentioned rare earth elements, Y, Sm, La, Ce, Pr, Nd, and Dy can appropriately improve the alkali resistance of the decorative film 30. In particular, Sm, La, Ce, Pr, Nd, and Dy can sufficiently improve the alkali resistance with a relatively small amount.

[0041] Here, in the ceramic product 1 according to this embodiment, in the FESEM-EDS analysis of the surface 30a of the decorative film 30, the mass concentration C N Mass concentration of rare earth elements C R The ratio of (C R / C N The second feature is that the above C is 0.01 or more and 0.18 or less. R / C N The decorative film 30 having a C value of 0.01 or more contains a certain amount of rare earth elements, which are factors that improve alkali resistance, in contrast to precious metal elements, which are factors that reduce alkali resistance, and therefore can maintain the alkali resistance within a suitable range.R / C N is preferably 0.012 or more, more preferably 0.014 or more, even more preferably 0.016 or more, and particularly preferably 0.018 or more. On the other hand, the decorative film 30 containing an excessive rare earth element may have a significantly reduced acid resistance. In consideration of such a reduction in acid resistance, in the ceramic product 1 according to this embodiment, the above C R / C N The upper limit of C is set to 0.18 or less. R / C N is preferably 0.17 or less, more preferably 0.16 or less, and even more preferably 0.15 or less. N is between 11% and 70% and C above is satisfied R / C N The mass concentration of rare earth elements C must be between 0.01 and 0.18. R For example, the mass concentration C of the rare earth element in the FESEM-EDS analysis of the surface 30a of the decorative film 30 is R may be 0.3% or more, 0.4% or more, or 0.5% or more. R The upper limit may be 7.5% or less, 6.0% or less, or 5.5% or less.

[0042] (b) First element Moreover, it is preferable that the decorative film 30 contains at least one of the first elements consisting of zirconium (Zr), titanium (Ti) and cobalt (Co). These first elements can contribute to further improving the chemical resistance of the decorative film 30. Although there is no intention to limit the technology disclosed herein, the reason why such an effect is obtained is presumed to be as follows. First, Zr is a zirconium oxide (ZrO 2 ) in the amorphous matrix, and Ti exists as titanium oxide (TiO 2 ) in the amorphous matrix. These ZrO 2 and TiO 2can be complexed with the framework of an amorphous matrix (e.g., silicate glass) as a network-modifying ion. And ZrO 2 and TiO 2 Since Co has extremely high chemical resistance as a single material, it remains even after other components are dissolved by exposure to alkaline chemicals, forming a coating, thereby contributing to improving the chemical resistance of the decorative film 30. On the other hand, Co is a cobalt oxide (CoO, Co 3 O 4 , Co 2 O 3 The cobalt oxide exists in the amorphous matrix in the form of at least one of the above. This cobalt oxide can also be combined with the skeleton of the amorphous matrix as an ion that modifies the mesh structure. Cobalt oxide can strengthen the adhesion between the noble metal region 32 and the amorphous region 34, thereby contributing to improving the chemical resistance of the decorative film 30.

[0043] However, the mass concentration C of the first element in the FESEM-EDS analysis of the surface 30a of the decorative film 30 is 1 If the amount of rare earth elements becomes too large, the mass concentration C R Since the above C R / C N From this viewpoint, it may be difficult to form a decorative film 30 having excellent alkali resistance and satisfying the above condition. R Mass concentration of the first element C 1 The ratio of (C 1 / C R ) is preferably 3 or less, more preferably 2.9 or less, further preferably 2.8 or less, and particularly preferably 2.7 or less. On the other hand, the decorative film 30 in this embodiment has the above C R / C N If the above condition is met, a certain level of chemical resistance can be achieved even if the first element is not included. 1 / C R The lower limit of C is not particularly limited. 1 / C R = 0. However, in order to adequately exert the effect of improving chemical resistance by the first element, C 1 / C RIt is preferable that the first element is contained so that the ratio is 0.1 or more (more preferably 0.2 or more, even more preferably 0.3 or more, and particularly preferably 0.4 or more).

[0044] The mass concentration of the first element C 1 However, from the viewpoint of more appropriately exerting the effect of improving chemical resistance by the first element, the mass concentration C of the first element is 1 is preferably 0.01% or more, more preferably 0.02% or more, and particularly preferably 0.03% or more. On the other hand, the mass concentration C R From the viewpoint of preventing a relative decrease in the mass concentration of the first element, C 1 is preferably 5% or less, more preferably 4% or less, further preferably 3% or less, and particularly preferably 2% or less.

[0045] (c) Second element Next, the matrix-forming elements may contain a metallic element or a semimetallic element other than the rare earth element and the first element, so long as they can form an appropriate amorphous matrix in the amorphous region 34. In this specification, such a matrix-forming element other than the rare earth element and the first element is referred to as a "second element." Hereinafter, Si, Al, and Bi will be described as examples of such a second element.

[0046] First, Si is silicon oxide (SiO 2 ) can constitute the framework of the amorphous matrix of the amorphous region 34. Note that, although this is not intended to limit the technology disclosed herein, the mass concentration C Si is preferably 10% or more, more preferably 15% or more, further preferably 17.5% or more, and particularly preferably 20% or more. This allows a strong amorphous matrix having an appropriate skeleton to be formed. On the other hand, from the viewpoint of ensuring sufficient amounts of other elements (rare earth elements, first element, etc.), the mass concentration C of Si is Si The upper limit of is preferably 60% or less, more preferably 59.5% or less, further preferably 59% or less, and particularly preferably 58.5% or less.

[0047] Next, a part of Al forms a complex oxide with other elements (Si, rare earth elements, etc.), which can contribute to improving the chemical resistance of the decorative film 30. Although this does not limit the technology disclosed herein, from the viewpoint of obtaining a decorative film 30 with better chemical resistance, the mass concentration C of Al in the FESEM-EDS analysis of the surface 30a of the decorative film 30 was Al is preferably 1% or more, more preferably 1.5% or more, further preferably 2% or more, and particularly preferably 2.5% or more. On the other hand, from the viewpoint of ensuring sufficient abundance of rare earth elements, the first element, etc., the mass concentration C Al The upper limit is preferably 15% or less, more preferably 14% or less, further preferably 13.5% or less, and particularly preferably 13% or less.

[0048] Bi is also known as bismuth oxide (Bi 2 O 3 ) form a part of the skeleton of the amorphous matrix of the amorphous region 34. 2 O 3 Since Bi has the effect of softening the amorphous material, it can contribute to improving the adhesion of the decorative film 30 to the ceramic product 1. In particular, when the decorative film 30 is formed on the surface of the coating layer 20 as in this embodiment, Bi 2 O 3 By diffusing to the coating layer 20 side, even higher fixation can be obtained. By improving the fixation, Bi can contribute to preventing peeling of the decorative film 30. From the viewpoint of more suitably exerting the fixation improving effect of Bi, the mass concentration C of Bi in the surface 30a of the decorative film 30 was determined by FESEM-EDS analysis. Bi is preferably 0.01% or more, more preferably 0.015% or more, and particularly preferably 0.05% or more. On the other hand, from the viewpoint of ensuring sufficient abundance of rare earth elements, the first element, etc., the mass concentration C of Bi is Bi is preferably 5% or less, more preferably 4.7% or less, even more preferably 4.5% or less, and particularly preferably 4% or less.

[0049] It should be noted that the above description is not intended to limit the second element to Si, Al, or Bi. Detailed description will be omitted since the effect of the technology disclosed herein is small. However, examples of second elements other than Si, Al, and Bi include Sn, Zn, Be, Mg, Ca, Sr, Ba, Li, Na, K, Rb, B, V, Fe, Cu, P, Ni, and Cr. The mass concentration C of the second element in FESEM-EDS analysis of the surface 30a of the decorative film 30 is 2 is preferably 88% or less, more preferably 80% or less, even more preferably 75% or less, and particularly preferably 70% or less. This makes it possible to prevent a relative decrease in the mass concentration of elements (rare earth elements, first element, etc.) that significantly affect the chemical resistance of the decorative film 30. On the other hand, the mass concentration C of the second element 2 The lower limit is not particularly limited, and may be 20% or more, 25% or more, or 30% or more.

[0050] (3) Nonmetallic elements Moreover, the decorative film 30 of the ceramic product 1 according to this embodiment may contain nonmetallic elements in addition to the metallic elements of the precious metal elements and the matrix-forming elements. For example, as described above, the matrix-forming elements are present in the amorphous region 34 in the form of oxides, so oxygen (O) may be present in the decorative film 30. In addition, as will be described in detail later, various organic materials are added to the decorative composition (paint), which is the precursor of the decorative film 30. The decorative film 30 after firing may contain nonmetallic elements derived from such organic materials. Examples of this type of nonmetallic element include carbon (C), sulfur (S), nitrogen (N), and phosphorus (P).

[0051] <Manufacturing method of ceramic products> Next, an example of a method for producing the ceramic product 1 according to this embodiment will be described. Note that the ceramic product disclosed herein is not limited to those produced by the following production method.

[0052] When manufacturing the ceramic product 1 according to this embodiment, first, a desired substrate 10 is prepared. For example, the substrate 10 can be prepared by molding and firing a substrate material in which predetermined ceramic components are mixed. The substrate 10 with a coating layer 20 as shown in FIG. 1 can be prepared by applying a glaze to the surface of the fired substrate 10 and then firing it again. However, this step is not particularly limited as long as the substrate 10 can be prepared. For example, a substrate 10 that has been separately produced may be purchased and prepared.

[0053] Next, in the manufacture of the ceramic product 1 according to this embodiment, the decorative film 30 is formed on the base material 10. In forming this decorative film 30, a desired pattern is drawn on the surface of the base material 10 using a decorative composition (paint) containing predetermined components, and then a firing process is carried out. In the firing process in this step, the firing temperature is preferably set in the range of 700°C to 1000°C. This allows the components of the decorative composition to be appropriately sintered to form the decorative film 30.

[0054] The decorative composition used in this embodiment is a paste-like composition containing a precious metal element and a matrix-forming element. The form of the precious metal element and the matrix-forming element in this decorative composition is not particularly limited. For example, the precious metal element and the matrix-forming element may be in the form of a metal resinate, a complex, a polymer, a solid (fine particle), or the like. Details of the precious metal element and the matrix-forming element contained in the decorative composition are omitted to avoid duplication.

[0055] In addition, when the firing process is performed in this step, the decorative composition may be mixed with some of the components of the underlayer (substrate 10 or coating layer 20) to which the decorative composition is applied. Therefore, the decorative film 30 after the firing process contains not only elements derived from the decorative composition but also elements derived from the underlayer. Furthermore, the degree to which the components of the underlayer are mixed into the decorative film may vary depending not only on the components of the decorative composition and the underlayer but also on the firing conditions (firing temperature, firing time, etc.). For this reason, when manufacturing the ceramic product disclosed herein, it is preferable to appropriately change various conditions such as the composition of the decorative composition, the composition of the underlayer, and the firing conditions, and appropriately conduct preliminary tests to investigate the conditions under which a ceramic product of the desired configuration is formed.

[0056] In addition to the precious metal element and the matrix-forming element, it is preferable that various components are added to the decorative composition in consideration of the fixation to the substrate surface, moldability, etc. Such additives can be any conventionally known components that can be used in decorative compositions, without particular limitation, as long as they do not significantly impede the effects of the technology disclosed herein. For example, when the precious metal element and the matrix-forming element are each contained in a metal resinate state, an organic compound for forming the metal resinate is added to the decorative composition. Such organic compounds can be any conventionally known resin materials that can be used to produce metal resinates, without particular limitation. Examples of such resin materials include carboxylic acids with a high carbon number (e.g., 8 or more carbon atoms), such as octylic acid (2-ethylhexanoic acid), abietic acid, naphthenic acid, stearic acid, oleic acid, linoleic acid, and neodecanoic acid; sulfonic acids; resin acids contained in rosin and the like; resin sulfur balsam containing essential oil components such as turpentine oil and lavender oil, alkyl mercaptides (alkyl thiolates), aryl mercaptides (aryl thiolates), mercaptocarboxylic acid esters, and alkoxides.

[0057] In addition, when the precious metal element and the matrix-forming element are each contained in a state of a metal resinate, it is preferable to use an organic solvent that disperses or dissolves the metal resinate. As such a solvent, those that have been used in resinate pastes and those that have been used in liquid gold solutions can be used without any particular limitation. Examples of the organic solvent include 1,4-dioxane, 1,8-cineol, 2-pyrrolidone, 2-phenylethanol, N-methyl-2-pyrrolidone, p-tolualdehyde, benzyl benzoate, butyl benzoate, eugenol, caprolactone, geraniol, methyl salicylate, cyclohexanone, cyclohexanol, cyclopentyl methyl ether, citronellal, di(2-chloroethyl)ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, dihydrocarvone, dibromomethane, dimethyl sulfoxide, dimethylformamide, nitrobenzene, pyrrolidone, propylene glycol monophenyl ether, pulegone, benzyl acetate, benzyl alcohol, benzaldehyde, turpentine oil, and lavender oil. These organic solvents may be used alone or in combination. Metal resinates are commercially available as resinate pastes, for example, and such resinate pastes may be used as they are.

[0058] The decorative composition may also contain other additive components, provided that they do not significantly impair the effects of the technology disclosed herein, such as organic binders, protective materials, surfactants, thickeners, pH adjusters, preservatives, defoamers, plasticizers, stabilizers, antioxidants, etc.

[0059] <Other embodiments> The above describes one embodiment of the technology disclosed herein. Note that the ceramic product 1 according to the above embodiment shows an example to which the technology disclosed herein is applied, and does not limit the technology disclosed herein.

[0060] For example, as shown in FIG. 1, the ceramic product 1 according to the embodiment described above has a coating layer 20 between the substrate 10 and the decorative film 30. However, the coating layer 20 is not an essential component of the ceramic product disclosed herein. That is, the decorative film may be formed directly on the surface of the ceramic substrate. According to the technology disclosed herein, even in a ceramic product in which a decorative film is formed directly on the substrate surface, a decorative film having sufficient chemical resistance can be formed. Another example of the ceramic product is one in which a matte layer in which a predetermined metal oxide particle (e.g., zircon particle) is dispersed is formed between the substrate and the decorative film, and the gloss of the decorative film is intentionally reduced. Another example of the ceramic product is one in which a paint layer is formed between the substrate and the coating layer to form a three-dimensional decorative film. The technology disclosed herein can be applied to ceramic products of these configurations without any particular restrictions.

[0061] As shown in FIG. 1, the ceramic product 1 according to the embodiment described above is a microwave-safe ceramic product in which a plurality of precious metal regions 32 are scattered in an amorphous region 34. However, the technology disclosed herein can contribute to the realization of a decorative film having excellent chemical resistance even in ceramic products other than those that are microwave-safe. However, since the microwave-safe ceramic product 1 shown in FIG. 1 has a very large amount of exposed amorphous regions 32, the phenomenon of the promotion of hydrolysis of the amorphous matrix due to the catalytic action of the precious metal elements is likely to manifest itself in the form of a significant decrease in the alkali resistance of the decorative film 30. The technology disclosed herein can appropriately suppress the decrease in alkali resistance due to the precious metal elements, and is therefore particularly suitable for use in microwave-safe ceramic products.

[0062] [Test example] Test examples relating to the technology disclosed herein will be described below, but it is not intended that the technology disclosed herein be limited to such test examples.

[0063] A. First test In this study, 19 typesCeramic products made using the decorative composition ( Example 1 to Example 7, Example 9 to Example 17, Example 19, Example 22 to Example 23 ) were prepared, and the performance of each ceramic product (acid resistance, alkali resistance, and gloss of the decorative film) was examined.

[0064] 1. Sample Preparation <Ceramics product manufacturing> In this test, a white porcelain plate (length: 15 mm, width: 15 mm) with a coating layer was prepared. A decorative composition containing a precious metal element and a matrix-forming element was applied to the entire surface of one side of the white porcelain plate. A spin coater (Opticoat MS-A-150) manufactured by Mikasa Co., Ltd. was used to apply the decorative composition, and the spinning conditions were adjusted so that the thickness of the decorative film after firing would be within the range of 30 nm to 250 nm. The white porcelain plate with the decorative composition applied was dried on a hot plate at 60°C for 1 hour, and then fired at 800°C for 10 minutes. This produced a ceramic product with a decorative film formed on the surface. The coating layer formed on the white porcelain plate was obtained by firing a glaze with the following composition at 1200°C.

[0065] [Glaze composition for forming coating layer] SiO 2 : 70.8wt% Al 2 O 3 : 16.39wt% Fe 2 O 3 :0.11wt% CaO: 4.2wt% MgO: 3.99wt% K 2 O: 3.36 wt% Na 2 O: 0.63wt% ZnO: 0.53wt%

[0066] And in this test, Example 1 to Example 7, Example 9 to Example 17, Example 19, Example 22 to Example 23In each of the above, the composition of the paint for forming the decorative film (decorative composition) was varied. In preparing the decorative composition, various raw materials were mixed in an ointment jar and mixed for 2 minutes at 1800 rpm using a mixer manufactured by Thinky Corporation (product name: Rotating and Revolving Awatori Mixer). Each decorative composition was then appropriately diluted so that the viscosity was in the range of 10 mPa·s to 15 mPa·s. The composition of the decorative composition used in each of Examples 1 to 23 is shown in Table 1. The elements shown in Table 1 were added to the decorative composition in the following forms.

[0067] [Form of each element in the decorative composition] Ag: Ag resinate (silver resinate) Au: Au resinate (gold resin sulfide balsam) Pt: Pt resinate (platinum resin sulfide balsam) Rh: Rh resinate (rhodium resin sulfide balsam) Al:Al resinates and aluminum complexes Ti: Titanium resinates and titanium complexes Co:Co resinate (cobalt resinate) Si:Si resinate (silicon resin acid salt) Bi: Bi resinate (bismuth resinate) Sm: Sm resinate (samarium resinate) Y: Y-resinate (yttrium resinate) La: La resinate (lanthanum resinate) Ce:Ce resinate (cerium resinate) Pr: Pr resinate (praseodymium resinate) Nd: Neodymium resinate Dy: Dy resinate (dysprosium resinate)

[0068] [Table 1]

[0069] 2.Evaluation Test <Mass concentration measurement> Example 1 to Example 7, Example 9 to Example 17, Example 19, Example 22 to Example 23 A test piece cut out from the ceramic product was fixed to a sample stage with carbon tape so that the decorative film was facing upwards, and was coated using an osmium plasma coater (Japan Laser Electronics Co., Ltd.: OPC80N). In this way, a measurement sample was prepared in which the surface of the decorative film was covered with osmium. The discharge voltage for coating was 1.2 kV, the degree of vacuum was 6 to 8 Pa, and the coating time was 10 seconds.

[0070] Next, a field emission scanning electron microscope (Hitachi High-Technologies Corporation: SU8230) and an energy dispersive X-ray analyzer (Horiba, Ltd., detector: X-Max80, software: EMAX ENERGY version 2.04) were used to obtain a qualitative analysis chart of each element on the surface of the decorative film of each example measurement sample. In this test, K-ray was used in the analysis of C, O, Na, Mg, Al, Si, K, Ca, Ti, Zn, Ga, and Co. In addition, L-ray was used in the analysis of Ba, Y, La, Ce, Pr, Nd, Sm, Dy, Pt, Au, and Rh, and M-ray was used in the analysis of Bi. Then, the mass concentration of each element was measured based on the qualitative analysis chart. In addition, the mass concentration of each element was calculated by automatic calculation (standardless method) by specifying only metal elements and semimetal elements as target elements in the "quantitative analysis" mode of the EMAX software. In addition, the detailed measurement conditions for the above FESEM-EDS analysis are as follows.

[0071] [Detection conditions] Field of view: 5000x Voltage applied: 15.0kV Emission current: 10μA Extraction voltage: 4.2kV Probe current setting: High Condenser lens 1:4.0 Working distance: 15.0±0.5mm

[0072] [Qualitative analysis conditions] Spectral collection time: 60 seconds Process time: 4 Spectral range: 0-20keV Number of channels: 2k

[0073] In this test, the mass concentration (%) of each element relative to the total number of atoms (100%) on the surface of the decorative film was calculated based on the qualitative analysis chart obtained under the above conditions. The calculation results are shown in Table 2.

[0074] [Table 2]

[0075] In addition, in this test, the mass concentration of each element was calculated based on the mass concentration of the measured elements. N " and "Mass concentration of precious metal elements C N Mass concentration of rare earth elements C R The ratio of (C R / C N ) and "mass concentration of rare earth elements C R Mass concentration of the first element C 1 The ratio of (C 1 / C R ) and "mass concentration of precious metal elements C N Mass concentration of Pt with respect to C Pt The ratio of (C Pt / C N The results of each calculation are shown in Table 3.

[0076] <Acid resistance evaluation> A 4 wt% aqueous solution of acetic acid was kept at room temperature (23-25°C) and the test piece was immersed in the aqueous solution for 24 hours. The test piece was then removed from the aqueous solution, washed with water, and subjected to a scratch test in which zircon paper was rubbed against the test piece 10 times to observe whether the decorative film was damaged. In this test, samples in which 30% or more of the decorative film remained were deemed to have sufficient acid resistance (○). The evaluation results are shown in Table 3.

[0077] <Alkaline resistance evaluation> In this test, 0.5 wt% Na was heated to 100℃ and boiled.2 CO 3 The test pieces of each example were immersed in the aqueous solution (3 L) for 30 minutes. After immersion, the test pieces were washed with water and subjected to a scratch test in which zircon paper was rubbed back and forth 10 times to observe whether the decorative film was damaged. In this test, the immersion time was extended in 30-minute increments, and the maximum immersion time at which 30% or more of the decorative film remained was regarded as the "durability time (h)". The durability time for each example is shown in Table 3.

[0078] <Gloss evaluation> The gloss value of the decorative part of each example was measured using a spectrophotometer. Specifically, a spectrophotometer (CM-700d) manufactured by Konica Minolta Sensing Inc. was used to measure the L* value, a* value, b* value, and gloss value representing 8° gloss in SCI and SCE modes. In this evaluation, decorative parts with a gloss value of 500 or more were evaluated as having a suitable gloss. The gloss values ​​of each example are shown in Table 3.

[0079] [Table 3]

[0080] As stated above, Example 1 to Example 7, Example 9 to Example 17 In Examples 22 and 23, a decorative film excellent in acid resistance, alkali resistance, and gloss value was formed. However, in Examples 22 and 23, most of the decorative film peeled off after being immersed in an alkaline solution for only 30 minutes. From this, it is considered that in order to ensure sufficient alkali resistance of the decorative film, R / C N It was found that it was necessary to secure a certain amount of C R / C N In Example 19, where the temperature was set too high, it was confirmed that the decorative film was easily peeled off by immersion in an acid solution. From this, it was found that rare earth elements have the effect of reducing the acid resistance of the decorative film, so in order to obtain a ceramic product with excellent overall chemical resistance, it is necessary to use C R / C N It was found that it was necessary to control 。

[0081] B. Second Test In this test, ceramic products were produced using the same decorative composition on six types of substrates with undercoats of different compositions (Examples 24 to 29). The acid resistance, alkali resistance, and gloss of the decorative film of each example were evaluated in the same manner as in the first test.

[0082] 1. Sample Preparation <Ceramics product manufacturing> In Examples 24 to 28, five types of white porcelain flat plates with coating layers of different compositions were prepared. In Example 29, a white porcelain flat plate was used on which a matte layer with dispersed Zr particles was formed on the surface. A decorative composition was applied to the surface of each substrate and fired to produce a ceramic product with a decorative film. The decorative composition used in this test was the same as that used in Example 6 of the first test. The conditions for applying the decorative composition and firing the composition were set to the same conditions as those in the first test.

[0083] In Examples 24 to 29, commercially available tableware was purchased and cut out to use as white porcelain plates, so the composition of the chemicals (glaze, etc.) used to form the underlayer (coat layer or matte layer) was unknown. For this reason, in this test, elemental analysis was performed using FESEM-EDS analysis on the surface of the white porcelain plate before the decorative film was formed to investigate the composition of the underlayer. The results of the FESEM-EDS analysis are shown in Table 4.

[0084] [Table 4]

[0085] 2.Evaluation Test In this test, (1) mass concentration measurement, (2) acid resistance evaluation, (3) alkali resistance evaluation, and (4) gloss evaluation were performed according to the same procedures as in the first test above. The results of the mass concentration measurement are shown in Table 5, and the results of the acid resistance evaluation, alkali resistance evaluation, and gloss evaluation are shown in Table 6. In Example 29, a matte layer was formed to intentionally reduce the gloss of the decorative film, so the gloss value was reduced to a level that could not be measured. For this reason, the gloss value column for Example 29 in Table 6 is marked with "-", meaning that it was not measurable.

[0086] In addition, in this test, as in the first test, the mass concentration of the precious metal elements C N " and "Mass concentration of precious metal elements C N Mass concentration of rare earth elements C R The ratio of (C R / C N ) and "mass concentration of rare earth elements C R Mass concentration of the first element C 1 The ratio of (C 1 / C R ) and "mass concentration of precious metal elements C N Mass concentration of Pt with respect to C Pt The ratio of (C Pt / C N The results of these calculations are shown in Table 6.

[0087] [Table 5]

[0088] [Table 6]

[0089] As described above, in Examples 24 to 29, the compositions of the decorative films after firing were different, even though the decorative compositions used were the same. This is presumably due to the fact that the decorative composition and part of the base layer were mixed during the firing process, and the constituent elements of the base layer were reflected in the FESEM-EDS analysis. However, in the FESEM-EDS analysis of the decorative films after firing, the mass concentration C N is 11% or more and 70% or less, and the mass concentration of precious metal elements C N Mass concentration of rare earth elements C R The ratio of (C R / C N It has been found that, when the ratio (R) is 0.01 or more and 0.18 or less, even if the decorative composition is mixed with the undercoat layer, a ceramic product having sufficient chemical resistance can be manufactured.

[0090] C. Third Test In this test, five types of decorative compositions with different compositions from those in the first test were prepared, and ceramic products were produced using each decorative composition (Examples 30 to 34). Then, the acid resistance, alkali resistance, and gloss of the decorative film of each example of the ceramic product were evaluated in the same manner as in the first and second tests.

[0091] 1. Sample Preparation In this test, a white porcelain plate having a coating layer (glaze) of the same composition as in the first test was prepared. A decorative composition was applied to the entire surface of one side of the white porcelain plate. A spin coater (Opticoat MS-A-150) manufactured by Mikasa Co., Ltd. was used to apply the decorative composition, and the spin conditions were adjusted so that the thickness of the decorative film after firing would be within the range of 30 nm to 250 nm. In this test, firing was performed under the same conditions as in the first test, except that the firing temperature was increased to 850°C. As a result, ceramic products with decorative films formed on the surfaces were produced (Examples 30 to 34). The compositions of the five types of decorative compositions used in this test are shown in Table 7 below.

[0092] [Table 7]

[0093] 2.Evaluation Test In this test, (1) mass concentration measurement, (2) acid resistance evaluation, (3) alkali resistance evaluation, and (4) gloss evaluation were performed according to the same procedures as in the first and second tests. The results of the mass concentration measurement are shown in Table 8, and the results of the acid resistance evaluation, alkali resistance evaluation, and gloss evaluation are shown in Table 9.

[0094] In addition, in this test, as in the first and second tests, the mass concentration of the precious metal elements C N " and "Mass concentration of precious metal elements C N Mass concentration of rare earth elements C R The ratio of (C R / C N ) and "mass concentration of rare earth elements C R Mass concentration of the first element C 1 The ratio of (C 1 / C R ) and "mass concentration of precious metal elements C N Mass concentration of Pt with respect to C Pt The ratio of (C Pt / C N The results of these calculations are shown in Table 9.

[0095] [Table 8]

[0096] [Table 9]

[0097] As shown in Table 8, in this test, not only in Example 31 (see Table 7) where bismuth (Bi) was not added to the decorative composition, but also in all of Examples 30 to 34, the presence of bismuth (Bi) was not confirmed in the decorative film. This is presumably because the increased firing temperature promoted the diffusion of Bi element during firing, resulting in a Bi concentration below the detection limit. Meanwhile, in all of Examples 30 to 34, decorative films were formed that had excellent acid resistance, alkali resistance, and gloss value. This indicates that the mass concentration C of the precious metal element N is within the range of 11% to 70% and C R / C N It was found that, as long as the bismuth ratio is within the range of 0.01 to 0.18, a decorative film having excellent chemical resistance and aesthetic appearance can be formed even if the Bi element is present at an extremely low concentration below the detection limit.

[0098] Although specific examples of the technology disclosed herein have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific examples exemplified above. [Explanation of symbols]

[0099] 1. Ceramic products 10 Base material 20 Coating Layer 30 Decorative Film 32 Precious metals area 34 Amorphous Region

Claims

1. A tableware having a decorative film containing a precious metal element and a matrix-forming element, The precious metal element contains at least platinum and rhodium, The matrix-forming elements contain at least a rare earth element, The mass concentration C of the precious metal element obtained in the FESEM-EDS analysis of the surface of the decorative film N is 11% or more and 70% or less, and The mass concentration C of the precious metal element N The mass concentration C of the rare earth element relative to R The ratio of (C R / C N ) is 0.01 or more and 0.18 or less, The decorative film has a thickness of 30 nm or more and 250 nm or less.

2. A tableware having a decorative film containing a precious metal element and a matrix-forming element, The precious metal element contains at least platinum, The matrix-forming elements contain at least a rare earth element, The mass concentration C N of the precious metal element obtained by FESEM-EDS analysis of the surface of the decorative film is 11% or more and 70% or less, and a ratio (C R / C N ) of a mass concentration C R of the rare earth element to a mass concentration C N of the precious metal element is 0.01 or more and 0.18 or less; The thickness of the decorative film is 30 nm or more and 250 nm or less, The matrix-forming elements further contain at least one first element selected from the group consisting of Zr, Ti, and Co; The ratio (C 1 / C R ) of the mass concentration C 1 of the first element to the mass concentration C R of the rare earth element obtained by FESEM-EDS analysis of the surface of the decorative film is 0.4 or more and 3 or less.

3. 2. The tableware of claim 1, wherein the matrix-forming elements further contain at least one first element selected from the group consisting of Zr, Ti, and Co.

4. The mass concentration C of the rare earth element obtained in the FESEM-EDS analysis of the surface of the decorative film R The mass concentration C of the first element 1 The ratio of (C 1 / C R 4. The tableware of claim 3, wherein the ratio of the number of pieces of the sieve to the number of pieces of the sieve is 3 or less.

5. The tableware according to claim 1 , wherein the decorative film further contains at least one precious metal element selected from the group consisting of Au, Pd, Ir, and Ag.

6. The mass concentration C of the precious metal element N The mass concentration C of Pt Pt The ratio of (C Pt / C N 3. The tableware according to claim 1, wherein the ratio of the thickness of the slab to the thickness of the container is 0.75 or more.

7. 3. The tableware according to claim 1, wherein the decorative film contains at least one rare earth element selected from the group consisting of Y, Sm, La, Ce, Pr, Nd, and Dy.

8. 3. The tableware according to claim 1, wherein the matrix-forming elements further contain at least one second element selected from the group consisting of Si, Al, K, Na, Mg, Ca, Ga, Ba, and Bi.

9. The tableware according to claim 1 or 2, wherein the decorative film comprises a precious metal region containing the precious metal element as a main component and an amorphous region containing the matrix-forming element as a main component, and a plurality of the precious metal regions are scattered in the amorphous region.

Citation Information

Patent Citations

  • Scratch processing material

    JP1988093567A

  • Build-up colors

    JP1994056558A

  • Noble metal surface decorating vessel usable for microwave oven, its production and liquid gold for insulating muffle painting

    JP1996183682A

  • Highly durable and highly chemical-resistant liquid gold for ceramic overglaze decoration

    JP2000128675A

  • Lustrous precious metal composition

    JP2002541056A